Chemotaxonomy, Morphology and Chemo Diversity of Scutellaria (Lamiaceae) Species in Zagros, Iran - Farzaneh Jafari Dehkordi; Navaz Kharazian (Journal of Sciences, Islamic Republic of Iran)
This study concerns to evaluate the morphological and flavonoid variations, and chemotaxonomy among seven Scutellaria species. The limits of Scutellaria species were disturbed by different factors including hybridization and polymorphism. For this purpose, 39 Scutellaria accessions were collected from different natural habitats of Zagros region, Iran. A total of 15 quantitative and 20 qualitative morphological characters were studied. Leaf flavonoids were extracted using MeOH solution. The flavonoid classes were investigated using thin layer chromatography, column chromatography, UV-spect and LC-MS/MS (liquid chromatography mass spectrometry). To detect the taxonomic status of Scutellaria species, statistical analyses such as cluster, dissimilarity tree, and ordination methods were applied. The results of this research showed five flavonoid classes in different Scutellaria species including isoflavone, flavone, flavanone, flavonol and chalcone. Based on the cluster analysis of flavonoid and morphological data, the members of Scutellaria section Scutellaria were accurately separated from those of Scutellaria section Lupulinaria. Our study revealed a relationship between Scutellaria patonii and Scutellaria multicaulis. Moreover, the trichomes such as strigose, lanate, tomentose, pannous in leaf and stem, petiole, calyx, the form of leaf apex, and inflorescence length were found as diagnostic characters. Based on our results, the flavonoid and morphological markers display the taxonomic status of inter and intra-specific levels in Scutellaria.